The Evolving Epidemiology of Helicobacter pylori Infection and Gastric Cancer - Jia-Qing Huang; Richard H Hunt (Canadian Journal of Gastroenterology)
The relationship between Helicobacter pylori infection and the risk of gastric cancer has been well established in the last decade. Four metaanalyses have found that the infection increases the risk of noncardia gastric cancer by 2- to 6-fold compared with noninfected control populations. However, the role of cagA strains of H pylori in relation to gastric cancer has not been evaluated systematically. We undertook a meta-analysis of epidemiological studies examining the relationship between infection with cagA-positive strains of H pylori and the risk of gastric cancer, and found that patients who are seropositive for cagA strains of H pylori are at an increased risk for developing noncardia gastric cancer compared with those with H pylori infection alone. Therefore, searching for cagA-positive strains of H pylori may help identify populations at a greater risk for developing gastric cancer.